2015
DOI: 10.4236/ce.2015.622242
|View full text |Cite
|
Sign up to set email alerts
|

Age, Maturity and Gender, and the Propensity towards Surface and Deep Learning Approaches amongst University Students

Abstract: The approach that a student takes towards their study has a substantial impact on the quality of their learning and academic success-a deep rather than surface approach more likely to be associated with academic success. Using the validated study processes questionnaire developed by Biggs et al. (2001), this study surveys over 500 undergraduate students across one university to examine patterns of learning approaches against age, maturity and gender. Analysis indicates that age is important in terms of the ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
8
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
11
8
2
Order By: Relevance
“…Regarding age, it was found that the older students are, the more open to experience, curious, and deep learners they are, and the higher their IL level. Similar to our findings, Lake and Boyd's (2015) findings have shown a positive and consistent relationship between older age and deep learning, and a negative and consistent relationship between younger age and surface learning. However, in contrast to our study, Stokes and Urquhart (2011) found that young students were more confident in their IL abilities than older students.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding age, it was found that the older students are, the more open to experience, curious, and deep learners they are, and the higher their IL level. Similar to our findings, Lake and Boyd's (2015) findings have shown a positive and consistent relationship between older age and deep learning, and a negative and consistent relationship between younger age and surface learning. However, in contrast to our study, Stokes and Urquhart (2011) found that young students were more confident in their IL abilities than older students.…”
Section: Discussionsupporting
confidence: 91%
“…However, the more students resisted change, the more they used surface learning strategy. A study that examined the learning strategies of students in relation to age and gender, concluded that a deep learning strategy is more prevalent among older students, and a surface learning strategy is more common among younger ones (Lake and Boyd, 2015).…”
Section: Learning Strategiesmentioning
confidence: 99%
“…Demetriadis and Pombortsis (2007) discuss how the nature of learning changes over the course of a degree, with earlier years being focused upon knowledge acquisition and facts, whilst later years require deeper critical thinking skills and the application of knowledge. Lake and Boyd (2015) also show that older students tend to adopt deep learning approaches compared to younger students who focus on surface learning and we can interpret our findings considering such work. In first year, the material on which students are examined on is largely taught in the lectures; therefore, familiarity with this specific content is key.…”
Section: Discussionsupporting
confidence: 67%
“…During this period, just before clerkships begin, medical students lose focus on their intrinsic motivation for medicine and concentrate on achieving a good exam result instead. This upholds the ndings of research into high-stakes testing in schools, which showed that high-stakes testing narrows the curriculum, diminishes teaching and learning quality, and encourages a strategic/surface approach to learning (21,22). It also resonates with the ndings of Tetik et al, who identi ed a slight reduction in deep approach for second-year students at two of the three medical schools they examined (12).…”
Section: Discussionsupporting
confidence: 75%